# 8x(-x-3)=0

## Simple and best practice solution for 8x(-x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 8x(-x-3)=0 equation:

Simplifying
8x(-1x + -3) = 0
Reorder the terms:
8x(-3 + -1x) = 0
(-3 * 8x + -1x * 8x) = 0
(-24x + -8x2) = 0
Solving
-24x + -8x2 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '-8x'.
-8x(3 + x) = 0
Ignore the factor -8.
Subproblem 1Set the factor 'x' equal to zero and attempt to solve:
Simplifying
x = 0
Solving
x = 0
Move all terms containing x to the left, all other terms to the right.
Simplifying
x = 0
Subproblem 2Set the factor '(3 + x)' equal to zero and attempt to solve:
Simplifying
3 + x = 0
Solving
3 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + x = 0 + -3
Combine like terms: 3 + -3 = 0
0 + x = 0 + -3
x = 0 + -3
Combine like terms: 0 + -3 = -3
x = -3
Simplifying
x = -3Solutionx = {0, -3}`